Novel Fractal DGSs for Band-gap Filter with Improved Q-factor - Gong, Yan-Yun; Wang, Ling; Wei, Kun; Zhang, Zhao-Lin (Společnost pro radioelektronické inženýrství, 2017)
This paper presents a novel fractal defected ground structure (FDGS) for designing high Q-factor band-gap filter. Key parameters of the proposed FDGS are studied. The decreased slot distance causes rapid increase in the filter Q-factor. The designed second iterative FDGS provides the band-gap property at 1.662 GHz with 3-dB bandwidth of 10.8 MHz and Q-factor 69.25. The rejection level of the second iterative FDGS is greater than 40 dB. The third iterative FDGS has smaller dimension than that of the second iterative FDGS. Moreover, the third iterative FDGS has two resonant frequencies with suppression levels of 33 dB and 26 dB. The Q-factors of the resonant frequencies are 24.22 and 27.36 respectively.
Keywords: High Q-factor; band-gap filter; defected ground structure; fractal structure